Hypothèses sur l’origine et la diffusion du complexe rituel du tlacaxipehualiztli - Anne-Marie Vié-Wohrer (Journal de la Société des Américanistes)
Hypothesis about origins and diffusion of the ritual process of tlacaxipehualiztli. This article tries to document similarities between rituals practised mostly by hunter-gatherers of the North of Middle America and one of the most famous Aztec ritual complex.